High-voltage insulator ceramic and preparation method and application thereof

CN122889530APending Publication Date: 2026-10-09GUANGZHOU POWER SUPPLY BUREAU GUANGDONG POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611023288.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,在传统配方体系内,这种优化带来的性能提升空间有限

Benefits of technology

[0035]本申请提供一种高压绝缘子陶瓷,通过引入特定比例的一维CNTs同轴管作为复合功能填料,其独特的一维结构能够在陶瓷晶界处构建连续网络,从而显著提升绝缘子陶瓷的弯曲强度;同时,该同轴管表面的BCN绝缘涂层有效阻隔了碳纳米管之间的直接接触,避免了导电通路的形成,进而在增强力学性能的基础上协同提高绝缘子陶瓷的击穿强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889530A_ABST
    Figure CN122889530A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of high-voltage insulator ceramics, and particularly relates to high-voltage insulator ceramics, a preparation method thereof and application. The application provides high-voltage insulator ceramics, which introduces one-dimensional CNTs coaxial tubes as composite functional fillers in a specific proportion, the unique one-dimensional structure of which can construct a continuous network at the ceramic grain boundary, thereby significantly improving the bending strength of the insulator ceramics; meanwhile, the BCN insulating coating on the surface of the coaxial tube effectively blocks the direct contact between the carbon nanotubes, avoids the formation of a conductive path, and further improves the breakdown strength of the insulator ceramics on the basis of enhancing the mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of high-voltage insulator technology, specifically relating to high-voltage insulator ceramics, their preparation methods, and applications. Background Technology

[0002] As power systems develop towards ultra-high voltage and large capacity, higher requirements are placed on the electrical insulation performance and mechanical strength of high-voltage ceramic insulators. During long-term operation, ceramic insulators must simultaneously withstand high electric field stress and mechanical loads. Insufficient breakdown strength or decreased bending strength are the main causes of their failure, seriously affecting the safe operation of the power grid.

[0003] Traditional methods for improving the performance of ceramic insulators mainly focus on optimizing the basic ceramic material ratio (such as adjusting the proportions of kaolin, feldspar, and quartz) and improving the sintering process, thereby increasing density to improve overall performance. However, within traditional formulation systems, the performance improvement potential resulting from such optimization is limited. In recent years, some studies have attempted to add nanofillers to the ceramic matrix to enhance interfacial bonding, but issues with the uniformity of nanofiller dispersion in the ceramic matrix and the interfacial bonding between the filler and the matrix limit the performance improvement effect.

[0004] How to simultaneously improve the breakdown strength and bending strength of insulator ceramics is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] Based on this, one embodiment of this application provides high-voltage insulator ceramics, their preparation method, and their applications.

[0006] This application provides a high-voltage insulator ceramic, the raw materials for which include basic ceramic material and composite functional filler;

[0007] The composite functional filler accounts for 0.1%-1.0% of the mass of the base ceramic material;

[0008] The composite functional filler includes a one-dimensional CNT coaxial tube;

[0009] The one-dimensional CNTs coaxial tube includes carbon nanotubes and a BCN crystal coating covering the outer surface of the carbon nanotubes.

[0010] In some embodiments, the thickness of the BCN crystal coating is 5nm-20nm.

[0011] In some embodiments, the base ceramic material comprises, by weight, 60-80 parts kaolin, 10-25 parts quartz, and 5-15 parts potassium feldspar.

[0012] This application also provides a method for preparing the aforementioned high-voltage insulator ceramic, comprising the following steps:

[0013] The composite functional filler is ultrasonically dispersed in a solvent to prepare a filler dispersion.

[0014] The base ceramic material and the filler dispersion are mixed, dried and shaped to prepare a green blank; and the green blank is subjected to heating sintering and shaping to prepare the high-voltage insulator ceramic.

[0015] In some embodiments, mixing the base ceramic material with the filler dispersion includes:

[0016] The base ceramic material is subjected to a first ball milling process, and then a second ball milling process is performed after adding the filler dispersion.

[0017] In some embodiments, prior to the first ball milling process, a step of adding a binder to the base ceramic material is included.

[0018] In some embodiments, the adhesive comprises polyvinyl alcohol.

[0019] In some embodiments, the polyvinyl alcohol accounts for 0.5%-0.8% of the mass of the base ceramic material.

[0020] In some embodiments, the conditions for the first ball milling treatment include: a time of 8 h to 10 h, a rotation speed of 200 r / min to 300 r / min, and a ball milling medium of zirconia balls.

[0021] In some embodiments, the conditions for the second ball milling treatment include: a time of 1 h to 2 h, a rotation speed of 200 r / min to 300 r / min, and a ball milling medium of zirconia balls.

[0022] In some embodiments, the method for preparing the composite functional filler includes:

[0023] Carbon nanotubes were placed in a buffer solution, and dopamine hydrochloride was added to induce a polymerization reaction, thus preparing polydopamine-modified carbon nanotubes; and

[0024] The polydopamine-modified carbon nanotubes, boric acid, and urea were mixed and sintered to prepare the one-dimensional CNTs coaxial tubes.

[0025] In some embodiments, the buffer solution comprises Tris-HCl buffer.

[0026] In some embodiments, the mass ratio of the polydopamine-modified carbon nanotubes, boric acid, and urea is 1:(1-3):(4-6).

[0027] In some embodiments, the conditions for the mixed sintering process include: a temperature of 1100℃-1200℃; a time of 2h-3h; and an inert gas atmosphere. In some embodiments, the inert gas is nitrogen.

[0028] In some embodiments, the molding process conditions include a pressure of 15 MPa - 25 MPa and a time of 1 min - 2 min.

[0029] In some embodiments, the ultrasonic dispersion process uses a power of 100W-300W for a duration of 25min-35min.

[0030] In some embodiments, the heating sintering process is a gradient heating sintering process, which includes a first heating stage, a second heating stage, and a third heating stage performed sequentially.

[0031] In some embodiments, the conditions for the first heating stage include: heating to 550°C-650°C at a rate of 4.5°C / min-5°C / min and holding at that temperature for 25 min-35 min.

[0032] In some embodiments, the conditions for the second heating stage include: heating to 1050°C-1150°C at a rate of 2.5°C / min-3.5°C / min and holding at that temperature for 25 min-35 min.

[0033] In some embodiments, the conditions for the third heating include: heating to 1200℃-1300℃ at a rate of 1.5℃ / min-2.5℃ / min and holding at that temperature for 2 h-3 h.

[0034] This application also provides the application of the aforementioned high-voltage insulator ceramics in the manufacture of external insulation products for high-voltage transmission lines and power station equipment.

[0035] This application provides a high-voltage insulator ceramic that introduces a specific ratio of one-dimensional CNTs coaxial tubes as a composite functional filler. Its unique one-dimensional structure can build a continuous network at the ceramic grain boundaries, thereby significantly improving the bending strength of the insulator ceramic. At the same time, the BCN insulating coating on the surface of the coaxial tube effectively blocks the direct contact between carbon nanotubes, avoiding the formation of conductive paths, and thus synergistically improves the breakdown strength of the insulator ceramic while enhancing its mechanical properties. Attached Figure Description

[0036] To more clearly illustrate the technical solutions in the embodiments of this application and to more completely understand this application and its beneficial effects, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0037] Figure 1 This is a process flow diagram of a method for preparing high-voltage insulator ceramics according to one embodiment of this application;

[0038] Figure 2 SEM images of CNTs@BCN coaxial tubes at different magnifications;

[0039] Figure 3 The electron energy loss spectra of elements B, C, and N are shown. Detailed Implementation

[0040] The present application will be further described in detail below with reference to the embodiments and examples. It should be understood that these embodiments and examples are for illustrative purposes only and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to enable a more thorough and comprehensive understanding of the disclosure of the present application. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various modifications or alterations without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. Furthermore, numerous specific details are set forth in the following description to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0041] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0042] Unless otherwise stated or in case of contradiction, the terms or phrases used herein shall have the following meanings:

[0043] The terms "and / or," "or / and," and "and / or" as used herein include any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or," "or / and," and "and / or," it should be understood that in this application, the technical solution undoubtedly includes technical solutions connected by "logical AND," and also undoubtedly includes technical solutions connected by "logical OR." For example, "A and / or B" includes three parallel solutions: A, B, and A+B. For example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, a technical solution that is connected by "logical OR"), as well as any and all combinations of A, B, C, and D, that is, combinations of any two or three of A, B, C, and D, and also combinations of all four of A, B, C, and D (that is, a technical solution that is connected by "logical AND").

[0044] In this application, the terms "multiple", "various", "multiple times", "multi-dimensional", etc., unless otherwise specified, refer to a quantity greater than or equal to 2. For example, "one or more" means one or more than or equal to two.

[0045] The terms “combinations of,” “any combination of,” and “any combination of” used in this article include all suitable combinations of any two or more of the listed items.

[0046] In this document, the term "suitable" as used in phrases such as "suitable combination," "suitable method," and "any suitable method" refers to the ability to implement the technical solution of this application, solve the technical problem of this application, and achieve the expected technical effect of this application.

[0047] In this application, terms such as "further," "even further," and "particularly" are used to describe purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.

[0048] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.

[0049] In this application, the technical features described in an open-ended manner include both closed technical solutions composed of the listed features and open technical solutions composed of the listed features.

[0050] In this application, numerical intervals (i.e., numerical ranges) are involved. Unless otherwise specified, the selected numerical distributions within the aforementioned numerical intervals are considered continuous and include the two endpoints (i.e., the minimum and maximum values) of the numerical range, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints. In this document, this is equivalent to directly listing every integer. For example, if t is an integer selected from 1 to 10, it means that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10. Furthermore, when multiple ranges are provided to describe features or characteristics, these ranges can be merged. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges to which they are included.

[0051] Unless otherwise specified, the temperature parameters in this application are permitted to be either constant-temperature treatment or variations within a certain temperature range. It should be understood that the constant-temperature treatment allows temperature fluctuations within the precision range of the instrument control, such as ±5℃, ±4℃, ±3℃, ±2℃, or ±1℃.

[0052] In this application, % (w / w) and wt% both represent weight percentage, % (v / v) refers to volume percentage, and % (w / v) refers to mass-volume percentage.

[0053] All references to documents mentioned in this application are incorporated herein by reference as if each document were individually incorporated herein by reference. Unless they conflict with the inventive purpose and / or technical solution of this application, all cited documents are incorporated herein by reference in their entirety and for all purposes. When citing documents in this application, the definitions of relevant technical features, terms, nouns, phrases, etc., are also incorporated herein by reference. When citing documents in this application, examples and preferred embodiments of the cited technical features may also be incorporated herein by reference, but only to the extent that they enable the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, this application shall prevail or modifications shall be made adaptably to the description in this application.

[0054] This application provides a high-voltage insulator ceramic, including a basic ceramic material and a composite functional filler;

[0055] The composite functional filler accounts for 0.1%-1.0% of the mass of the base ceramic material;

[0056] Composite functional packings include one-dimensional CNTs in coaxial tubes;

[0057] One-dimensional CNTs coaxial tubes include carbon nanotubes and a BCN crystal coating on the outer surface of the carbon nanotubes.

[0058] In the technical solution provided in this application, the composite functional filler adopts one-dimensional CNTs coaxial tubes with a BCN coating. The one-dimensional CNTs coaxial tubes form a continuous network structure in the ceramic matrix, effectively dispersed at grain boundaries, playing a bridging and reinforcing role, thereby improving the flexural strength of the material. Simultaneously, the BCN crystal coating has excellent electrical insulation properties, preventing direct contact between carbon nanotubes and the formation of conductive pathways, thus enhancing mechanical properties without reducing or even increasing the breakdown strength of the material.

[0059] For example, the percentage of composite functional filler in the mass of the base ceramic material can be 0.1%, 0.2%, 0.3%, 0.5%, 0.8%, or 1.0%, or any value thereof.

[0060] In some embodiments, the thickness of the BCN crystal coating is 5 nm to 20 nm. The thickness of the BCN crystal coating of the one-dimensional CNT coaxial tube can be selected from any value of 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, or 20 nm.

[0061] In some embodiments, the base ceramic material comprises, by weight, 60-80 parts kaolin, 10-25 parts quartz, and 5-15 parts potassium feldspar.

[0062] For example, kaolin in 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, or 80 parts, or any value in between; quartz in 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25 parts; potassium feldspar in 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 parts, or any value in between.

[0063] Another aspect of this application provides a method for preparing high-voltage insulator ceramics, comprising the following steps:

[0064] S1. The composite functional filler is ultrasonically dispersed in a solvent to prepare a filler dispersion.

[0065] S2. Mix the base ceramic material and the filler dispersion, and after drying and molding, prepare a green body; and

[0066] S3. The green blank is subjected to heating sintering and forming treatment to prepare the high-voltage insulator ceramic.

[0067] In some embodiments, mixing the base ceramic material with the filler dispersion includes: performing a first ball milling treatment on the base ceramic material, and then performing a second ball milling treatment after adding the filler dispersion.

[0068] In some embodiments, prior to the first ball milling process, a step of adding a binder to the base ceramic material is included.

[0069] In some embodiments, the adhesive includes polyvinyl alcohol.

[0070] In some embodiments, polyvinyl alcohol constitutes 0.5%-0.8% of the mass of the base ceramic material. For example, the mass percentage of polyvinyl alcohol in the base ceramic material is 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, or 0.8%, or any value in between.

[0071] In some embodiments, the preparation method of the composite functional filler includes: placing carbon nanotubes in a buffer solution, adding dopamine hydrochloride and carrying out a polymerization reaction to prepare polydopamine-modified carbon nanotubes; and mixing polydopamine-modified carbon nanotubes, boric acid and urea and then carrying out sintering treatment to prepare one-dimensional CNTs coaxial tubes.

[0072] In some of these embodiments, the buffer solution includes Tris-HCl buffer.

[0073] In some embodiments, the mass ratio of polydopamine-modified carbon nanotubes, boric acid, and urea is 1:(1-3):(4-6).

[0074] In some embodiments, the sintering conditions include: a temperature of 1100℃-1200℃; a time of 2h-3h; and an inert gas atmosphere. The sintering temperature can be selected from 1100℃, 1120℃, 1150℃, 1180℃, or 1200℃, or any value in between; the holding time can be selected from 2h, 2.5h, or 3h, or any value in between.

[0075] In some embodiments, the inert gas is nitrogen.

[0076] In some embodiments, the conditions for the first ball milling treatment include: a time of 8-10 hours, a rotation speed of 200-300 r / min, and zirconia balls as the milling medium. The time for the first ball milling treatment can be selected from 8 hours, 8.5 hours, 9 hours, 9.5 hours, or 10 hours, or any value in between; the time for the second ball milling treatment can be selected from 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, or 2 hours, or any value in between; and the rotation speed for the ball milling treatment can be selected from 200 r / min, 220 r / min, 250 r / min, 280 r / min, or 300 r / min, or any value in between. For example, the zirconia balls can include one or more of the following sizes: 5 mm, 8 mm, and 10 mm.

[0077] In some of these embodiments, the solvent may be anhydrous ethanol.

[0078] In some embodiments, the conditions for the second ball milling process include: a time of 1 h to 2 h, a rotation speed of 200 r / min to 300 r / min, and the milling media being zirconia balls.

[0079] In some embodiments, the molding process conditions include: a pressure of 15 MPa - 25 MPa and a holding time of 1 min - 2 min. The molding pressure can be selected from 15 MPa, 18 MPa, 20 MPa, 22 MPa, or 25 MPa and any value in between; the holding time can be selected from 1 min, 1.2 min, 1.5 min, 1.8 min, or 2 min and any value in between.

[0080] In some embodiments, the ultrasonic dispersion process uses a power of 100W-300W for a duration of 25min-35min.

[0081] In some embodiments, the heating sintering process includes a gradient heating sintering process, comprising a first heating stage, a second heating stage, and a third heating stage performed sequentially.

[0082] In some embodiments, the conditions for the first heating stage include: heating to 550°C-650°C at a rate of 4.5°C / min-5°C / min and holding at that temperature for 25 min-35 min.

[0083] In some embodiments, the conditions for the second heating stage include: heating to 1050°C-1150°C at a rate of 2.5°C / min-3.5°C / min and holding at that temperature for 25 min-35 min.

[0084] In some embodiments, the third heating conditions include: heating to 1200°C-1300°C at a rate of 1.5°C / min-2.5°C / min and holding at that temperature for 2-3 hours.

[0085] In some embodiments, during segmented heating sintering: the heating rate of the first heating stage can be selected from 4.5℃ / min, 4.8℃ / min, or 5℃ / min; the target temperature can be selected from 550℃, 580℃, 600℃, 620℃, or 650℃; and the holding time can be selected from 25min, 28min, 30min, 32min, or 35min. The heating rate of the second heating stage can be selected from 2.5℃ / min, 2.8℃ / min, 3.0℃ / min, 3.2℃ / min, or 3.5℃ / min; the target temperature can be selected from 1050℃, 1080℃, 1100℃, 1120℃, or 1150℃; and the holding time can be selected from 25min, 28min, 30min, 32min, or 35min. The heating rate of the third heating stage can be selected from 1.5℃ / min, 1.8℃ / min, 2.0℃ / min, 2.2℃ / min, and 2.5℃ / min; the target temperature can be selected from 1200℃, 1220℃, 1250℃, 1280℃, and 1300℃; and the holding time can be selected from 2.0h, 2.2h, 2.5h, 2.8h, and 3.0h.

[0086] This application also provides the application of the aforementioned high-voltage insulator ceramics in the manufacture of external insulation products for high-voltage transmission lines and power station equipment.

[0087] The preparation method described in this application only requires adding a filler dispersion step to the traditional insulator ceramic production line, without the need for additional large-scale equipment, and has excellent prospects for industrial application.

[0088] The embodiments of this application will be described in detail below with reference to examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application, or follow experimental manuals or conventional conditions in the art, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0089] In the specific embodiments described below, the measurement parameters involving raw material components may have slight deviations within the weighing accuracy range unless otherwise specified. For temperature and time parameters, acceptable deviations due to instrument testing accuracy or operational precision are permissible.

[0090] It should be understood that in the various embodiments of this application, the order of the above-mentioned processes does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0091] Example 1

[0092] This embodiment provides a method for preparing high-voltage insulator ceramics.

[0093] (1) Preparation of CNTs coaxial tubes: Weigh 1g of multi-walled carbon nanotubes and add them to 1000mL of Tris-HCl buffer solution (pH=8.5). Disperse the mixture by ultrasonication at 200W for 30min. Add 2g of dopamine hydrochloride and stir at room temperature for 24h. Filter the mixture, wash it with deionized water until neutral, and dry it under vacuum at 60℃ to obtain polydopamine-modified carbon nanotubes. Weigh 1g of polydopamine-modified carbon nanotubes, 2g of boric acid, and 5g of urea. Grind and mix them evenly. Place the mixture in a tube furnace and heat it to 1200℃ at 5℃ / min under a nitrogen atmosphere. Hold the temperature for 2h and allow it to cool naturally to obtain one-dimensional CNTs coaxial tubes (BCN coating thickness is about 12nm).

[0094] (2) Preparation of composite raw materials: Weigh 75 parts of kaolin, 15 parts of quartz, and 10 parts of potassium feldspar by mass and mix them as the base ceramic material. Weigh 0.1 wt% of the one-dimensional CNTs coaxial tube prepared in step (1) according to the total mass of the base ceramic material. Add the one-dimensional CNTs coaxial tube to anhydrous ethanol and ultrasonically disperse for 1 h to obtain a uniform filler dispersion. Add the base ceramic material to a ball mill jar and use zirconia balls of 5 mm, 8 mm, and 10 mm in a mass ratio of 1:1:1 as the ball milling medium according to the material:ball:anhydrous ethanol ratio of 1:2:1. Ball mill at 250 r / min for 8 h. Then add the filler dispersion and continue ball milling for 2 h under the same conditions. After ball milling, dry at 80℃ and pass through a 40-mesh sieve to obtain composite raw material powder. Add 0.6 wt% of polyvinyl alcohol according to the mass of the base ceramic material, mix evenly, and pass through a 40-mesh sieve again.

[0095] (3) Compression molding: Take the above composite raw material and press it into a circular sample with a diameter of 10 mm and a thickness of 1 mm under a pressure of 20 MPa. Hold the pressure for 1.5 min to obtain the blank.

[0096] (4) Sintering treatment: The green blank is placed in a muffle furnace and sintered by segmented heating. First heating stage: heating to 600℃ at 5℃ / min and holding for 30min; Second heating stage: heating to 1100℃ at 3℃ / min and holding for 30min; Third heating stage: heating to 1300℃ at 2℃ / min and holding for 2.5h; then cooling with the furnace to obtain high voltage insulator ceramic.

[0097] Example 2

[0098] This embodiment provides a method for preparing high-voltage insulator ceramics, which is basically the same as that in embodiment 1, except that in step (2), the one-dimensional CNTs coaxial tube accounts for 0.3 wt% of the total mass of the base ceramic material.

[0099] (1) Preparation of CNTs coaxial tubes: Weigh 1g of multi-walled carbon nanotubes and add them to 1000mL of Tris-HCl buffer solution (pH=8.5). Disperse the mixture by ultrasonication at 300W for 30min. Add 2g of dopamine hydrochloride and stir at room temperature for 24h. Filter the mixture, wash it with deionized water until neutral, and dry it under vacuum at 60℃ to obtain polydopamine-modified carbon nanotubes. Weigh 1g of polydopamine-modified carbon nanotubes, 2g of boric acid, and 5g of urea. Grind and mix them evenly. Place the mixture in a tube furnace and heat it to 1200℃ at 5℃ / min under a nitrogen atmosphere. Hold the temperature for 2h and cool it naturally to obtain one-dimensional CNTs coaxial tubes (BCN coating thickness is about 12nm).

[0100] (2) Preparation of composite raw materials: The composition of the basic ceramic material is the same as in Example 1. Weigh 0.3 wt% of one-dimensional CNTs coaxial tubes, which account for 0.3 wt% of the total mass of the basic ceramic material. Add it to anhydrous ethanol and ultrasonically disperse for 1 h to obtain a filler dispersion. Add the basic ceramic material to a ball mill jar and use zirconia balls of 5 mm, 8 mm and 10 mm in a mass ratio of 1:1:1 as the ball milling medium at 250 r / min for 8 h. Then add the filler dispersion and continue ball milling for 2 h. After ball milling, dry at 80℃, pass through a 40 mesh sieve, add 0.6 wt% of polyvinyl alcohol, mix evenly and pass through a 40 mesh sieve again.

[0101] (3) Compression molding: Take the above composite raw material and press it into a circular sample with a diameter of 10 mm and a thickness of 1 mm under a pressure of 20 MPa. Hold the pressure for 1.5 min to obtain the blank.

[0102] (4) Sintering treatment: The green blank is placed in a muffle furnace and sintered by segmented heating. First heating stage: heating to 600℃ at 5℃ / min and holding for 30min; Second heating stage: heating to 1100℃ at 3℃ / min and holding for 30min; Third heating stage: heating to 1300℃ at 2℃ / min and holding for 2.5h; then cooling with the furnace to obtain high voltage insulator ceramic.

[0103] Example 3

[0104] This embodiment provides a method for preparing high-voltage insulator ceramics, which is basically the same as that in embodiment 1, except that in step (2), the one-dimensional CNTs coaxial tube accounts for 0.8 wt% of the total mass of the base ceramic material.

[0105] (1) Preparation of CNTs coaxial tubes: Weigh 1g of multi-walled carbon nanotubes and add them to 1000mL of Tris-HCl buffer solution (pH=8.5). Disperse the mixture by ultrasonication at 100W for 30min. Add 2g of dopamine hydrochloride and stir at room temperature for 24h. Filter the mixture, wash it with deionized water until neutral, and dry it under vacuum at 60℃ to obtain polydopamine-modified carbon nanotubes. Weigh 1g of polydopamine-modified carbon nanotubes, 2g of boric acid, and 5g of urea. Grind and mix them evenly. Place the mixture in a tube furnace and heat it to 1200℃ at 5℃ / min under a nitrogen atmosphere. Hold the temperature for 2h and cool it naturally to obtain one-dimensional CNTs coaxial tubes (BCN coating thickness is about 12nm).

[0106] (2) Preparation of composite raw materials: The composition of the basic ceramic material is the same as in Example 1. Weigh 0.8 wt% of one-dimensional CNTs coaxial tubes, which account for 0.8 wt% of the total mass of the basic ceramic material. Add it to anhydrous ethanol and ultrasonically disperse for 1 h to obtain a filler dispersion. Add the basic ceramic material to a ball mill jar and use zirconia balls of 5 mm, 8 mm and 10 mm in a mass ratio of 1:1:1 as the ball milling medium at 250 r / min for 8 h. Then add the filler dispersion and continue ball milling for 2 h. After ball milling, dry at 80℃, pass through a 40 mesh sieve, add 0.6 wt% of polyvinyl alcohol, mix evenly and pass through a 40 mesh sieve again.

[0107] (3) Compression molding: Take the above composite raw material and press it into a circular sample with a diameter of 10 mm and a thickness of 1 mm under a pressure of 20 MPa. Hold the pressure for 1.5 min to obtain the blank.

[0108] (4) Sintering treatment: The green blank is placed in a muffle furnace and sintered by segmented heating. First heating stage: heating to 600℃ at 5℃ / min and holding for 30min; Second heating stage: heating to 1100℃ at 3℃ / min and holding for 30min; Third heating stage: heating to 1300℃ at 2℃ / min and holding for 2.5h; then cooling with the furnace to obtain high voltage insulator ceramic.

[0109] Comparative Example 1

[0110] This comparative example provides a method for preparing high-voltage insulator ceramics.

[0111] Difference from Example 1: This comparative example does not add any composite functional filler (one-dimensional CNTs coaxial tube), and the basic ceramic composition is the same as that of Example 1.

[0112] (1) The preparation step of CNTs coaxial tube is not performed.

[0113] (2) Preparation of composite raw materials: Weigh 75 parts of kaolin, 15 parts of quartz, and 10 parts of potassium feldspar by mass and mix them as the base ceramic material. Add the base ceramic material to a ball mill jar and use zirconia balls of 5mm, 8mm, and 10mm in a mass ratio of 1:1:1 as the ball milling medium at a speed of 250r / min for 10h. After ball milling, dry at 80℃, pass through a 40-mesh sieve, add 0.6 wt% polyvinyl alcohol of the base ceramic material, mix evenly, and pass through a 40-mesh sieve again.

[0114] (3) Compression molding: Take the above composite raw material and press it into a circular sample with a diameter of 10 mm and a thickness of 1 mm under a pressure of 20 MPa. Hold the pressure for 1.5 min to obtain the blank.

[0115] (4) Sintering treatment: The green blank is placed in a muffle furnace and sintered by segmented heating. First heating stage: heating to 600℃ at 5℃ / min and holding for 30min; Second heating stage: heating to 1100℃ at 3℃ / min and holding for 30min; Third heating stage: heating to 1300℃ at 2℃ / min and holding for 2.5h; then cooling with the furnace to obtain high voltage insulator ceramic.

[0116] Comparative Example 2

[0117] This comparative example provides a method for preparing high-voltage insulator ceramics.

[0118] Difference from Example 1: The composite functional filler in this comparative example is a regular multi-walled carbon nanotube without BCN coating, rather than a one-dimensional CNT coaxial tube.

[0119] (1) Pretreatment of ordinary carbon nanotubes: Weigh 1g of multi-walled carbon nanotubes, add them to 1000mL of anhydrous ethanol, sonicate for 30min, filter, vacuum dry at 60℃, and set aside.

[0120] (2) Preparation of composite raw materials: The composition of the basic ceramic material (75 parts kaolin, 15 parts quartz, 10 parts potassium feldspar) is the same as in Example 1. Weigh 0.3 wt% of the multi-walled carbon nanotubes pretreated in step (1) according to the total mass of the basic ceramic material. Add the multi-walled carbon nanotubes to anhydrous ethanol and ultrasonically disperse them for 1 h at 200 W to obtain a filler dispersion. Add the basic ceramic material to a ball mill jar and use zirconia balls of 5 mm, 8 mm and 10 mm in a mass ratio of 1:1:1 as the ball milling medium according to the ratio of material:ball:anhydrous ethanol = 1:2:1. Ball mill at 250 r / min for 8 h. Then add the filler dispersion and continue ball milling for 2 h. After ball milling, dry at 80℃, pass through a 40 mesh sieve, add 0.6 wt% of polyvinyl alcohol according to the mass of the basic ceramic material, mix evenly and pass through a 40 mesh sieve again to obtain the composite raw material.

[0121] (3) Compression molding: Take the above composite raw material and press it into a circular sample with a diameter of 10 mm and a thickness of 1 mm under a pressure of 20 MPa. Hold the pressure for 1.5 min to obtain the blank.

[0122] (4) Sintering treatment: The green blank is placed in a muffle furnace and sintered by segmented heating. First heating stage: heating to 600℃ at 5℃ / min and holding for 30min; Second heating stage: heating to 1100℃ at 3℃ / min and holding for 30min; Third heating stage: heating to 1300℃ at 2℃ / min and holding for 2.5h; then cooling with the furnace to obtain high voltage insulator ceramic.

[0123] Comparative Example 3

[0124] This comparative example provides a method for preparing high-voltage insulator ceramics.

[0125] Difference from Example 1: In this comparative example, the amount of one-dimensional CNTs coaxial tubes added accounts for 2.0 wt% of the total mass of the base ceramic material.

[0126] (1) Preparation of CNTs coaxial tube: Same as step (1) in Example 1.

[0127] (2) Preparation of composite raw materials: The composition of the basic ceramic material is the same as in Example 1. Weigh 2.0 wt% of one-dimensional CNTs coaxial tubes, which account for 2.0 wt% of the total mass of the basic ceramic material. Add the one-dimensional CNTs coaxial tubes to anhydrous ethanol and ultrasonically disperse for 1 h to obtain a filler dispersion. Add the basic ceramic material to a ball mill jar and use zirconia balls of 5 mm, 8 mm, and 10 mm in a mass ratio of 1:1:1 as the ball milling medium at 250 r / min for 8 h. Then add the filler dispersion and continue ball milling for 2 h. After ball milling, dry at 80 °C, pass through a 40 mesh sieve, add 0.6 wt% of polyvinyl alcohol, mix evenly, and pass through a 40 mesh sieve again to obtain the composite raw material.

[0128] (3) Compression molding: Take the above composite raw material and press it into a circular sample with a diameter of 10 mm and a thickness of 1 mm under a pressure of 20 MPa. Hold the pressure for 1.5 min to obtain the blank.

[0129] (4) Sintering treatment: The green blank is placed in a muffle furnace and sintered by segmented heating. First heating stage: heating to 600℃ at 5℃ / min and holding for 30min; Second heating stage: heating to 1100℃ at 3℃ / min and holding for 30min; Third heating stage: heating to 1300℃ at 2℃ / min and holding for 2.5h; then cooling with the furnace to obtain high voltage insulator ceramic.

[0130] Comparative Example 4

[0131] This comparative example provides a method for preparing high-voltage insulator ceramics.

[0132] The difference from Example 1: The sintering process in this comparative example uses the conventional one-step sintering method, rather than segmented heating sintering.

[0133] (1) Preparation of CNTs coaxial tube: Same as step (1) in Example 1.

[0134] (2) Preparation of composite raw materials: Same as step (2) in Example 1, with the amount of one-dimensional CNTs coaxial tube added being 0.3 wt%.

[0135] (3) Compression molding: Same as step (3) in Example 1.

[0136] (4) Sintering treatment: The green blank is placed in a muffle furnace and heated directly to 1300℃ at a rate of 3℃ / min, held for 2h, and then cooled with the furnace to obtain high voltage insulator ceramic.

[0137] Performance testing:

[0138] The high-voltage insulator ceramics prepared in the examples and comparative examples were subjected to the following tests:

[0139] (1) Breakdown strength test: The breakdown strength test shall be conducted in accordance with the standard GB / T 1408.1-2016 "Electrical strength test method for insulating materials - Part 1: Test under power frequency".

[0140] (2) Bending strength test: The bending strength test was carried out in accordance with the standard GB / T 8411.2-2008 "Ceramic and glass insulating materials - Part 2: Test methods". The test results are shown in Table 1.

[0141] Table 1

[0142]

[0143] Results Analysis: Based on the combined data from the embodiments and comparative examples, this application significantly improves the breakdown strength and flexural strength of high-voltage insulator ceramics by introducing "BCN-coated one-dimensional CNTs coaxial tubes" as composite functional fillers and employing a segmented heating sintering process. In terms of addition amount, the performance of Examples 1-3 continuously improves with increasing coaxial tube addition amount. Example 3 (0.8 wt%) exhibits the best performance, with a breakdown strength of 16.8 kV / mm and a flexural strength of 159 MPa, representing increases of 50% and 22.3% respectively compared to the control group (without filler) in Comparative Example 1. However, the breakdown strength (15.9 kV / mm) and flexural strength (151 MPa) of Comparative Example 3 (addition amount increased to 2.0 wt%) are lower than those of Example 3, indicating that excessive addition leads to filler agglomeration and increased porosity, suggesting an optimal addition amount window (approximately 0.8 wt%). From the key comparisons of the comparative examples, the breakdown strength of Comparative Example 2 (with the addition of ordinary CNTs without BCN coating) dropped sharply to 8.7 kV / mm, even far lower than the 11.2 kV / mm of the blank group. This is because the exposed conductive CNTs formed conductive pathways in the ceramic matrix, which seriously degraded the insulation performance. This, in turn, verifies the core and necessary role of the BCN insulating coating in blocking electron transmission and maintaining high breakdown strength. Comparative Example 4 (using a one-step direct sintering method instead of segmented heating) showed significantly lower breakdown strength (13.4 kV / mm) and flexural strength (142 MPa) than Example 2 (15.1 kV / mm, 150 MPa) at the same 0.3 wt% addition amount. This confirms that the segmented heating process is more conducive to the full discharge of organic matter in the green body and the uniform and dense growth of ceramic grains.

[0144] In summary, the addition of coaxial tubes combined with the three-stage segmented sintering process can significantly improve the flexural strength of insulator ceramics. At the same time, the BCN insulating coating on the surface of the coaxial tubes effectively blocks the direct contact between carbon nanotubes, avoiding the formation of conductive paths, thereby synergistically improving the breakdown strength of insulator ceramics while enhancing mechanical properties.

[0145] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. Furthermore, it should be understood that after reading the above teachings of this application, those skilled in the art can make various alterations or modifications to this application, and the equivalent forms obtained also fall within the scope of protection of this application. It should also be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. A high-voltage insulator ceramic, characterized in that, Its raw materials include basic ceramic materials and composite functional fillers; The composite functional filler accounts for 0.1%-1.0% of the mass of the base ceramic material; The composite functional filler includes a one-dimensional CNT coaxial tube; The one-dimensional CNTs coaxial tube includes carbon nanotubes and a BCN crystal coating covering the outer surface of the carbon nanotubes.

2. The high-voltage insulator ceramic according to claim 1, characterized in that, The thickness of the BCN crystal coating is 5nm-20nm.

3. The high-voltage insulator ceramic according to claim 1, characterized in that, The basic ceramic material, by weight, includes: 60-80 parts kaolin, 10-25 parts quartz, and 5-15 parts potassium feldspar.

4. The method for preparing high-voltage insulator ceramics according to any one of claims 1 to 3, characterized in that, Includes the following steps: The composite functional filler is ultrasonically dispersed in a solvent to prepare a filler dispersion. The base ceramic material and the filler dispersion are mixed, dried, and then a green body is prepared; and The green blank is subjected to heating sintering and forming processes to prepare the high-voltage insulator ceramic.

5. The method for preparing high-voltage insulator ceramics according to claim 4, characterized in that, Mixing the base ceramic material with the filler dispersion includes: The base ceramic material is subjected to a first ball milling process, and then a second ball milling process is performed after adding the filler dispersion. Optionally, prior to the first ball milling process, a step of adding a binder to the base ceramic material is also included; Optionally, the adhesive comprises polyvinyl alcohol; Optionally, the polyvinyl alcohol accounts for 0.5%-0.8% of the mass of the base ceramic material; Optionally, the conditions for the first ball milling treatment include: a time of 8 h to 10 h, a rotation speed of 200 r / min to 300 r / min, and a ball milling medium of zirconia balls; Optionally, the conditions for the second ball milling treatment include: a time of 1 h to 2 h, a rotation speed of 200 r / min to 300 r / min, and a ball milling medium of zirconia balls.

6. The method for preparing high-voltage insulator ceramics according to claim 4, characterized in that, The preparation method of the composite functional filler includes: Carbon nanotubes were placed in a buffer solution, and dopamine hydrochloride was added to induce a polymerization reaction, thus preparing polydopamine-modified carbon nanotubes; and The polydopamine-modified carbon nanotubes, boric acid, and urea were mixed and sintered to prepare the one-dimensional CNTs coaxial tubes.

7. The method for preparing high-voltage insulator ceramics according to claim 6, characterized in that, The method satisfies one or more of the following conditions: (1) The buffer solution includes Tris-HCl buffer solution; (2) The mass ratio of the polydopamine-modified carbon nanotubes, boric acid and urea is 1:(1-3):(4-6); as well as (3) The conditions for mixed sintering treatment include: temperature of 1100℃-1200℃; time of 2h-3h; and inert gas atmosphere. Optionally, the inert gas is nitrogen.

8. The method for preparing high-voltage insulator ceramics according to any one of claims 4 to 7, characterized in that, The molding process conditions include: pressure of 15 MPa - 25 MPa, time of 1 min - 2 min; and / or The ultrasonic dispersion treatment power is 100W-300W, and the time is 25min-35min.

9. The method for preparing high-voltage insulator ceramics according to any one of claims 4 to 7, characterized in that, The heating sintering process is a gradient heating sintering process, which includes a first heating stage, a second heating stage, and a third heating stage performed sequentially: The conditions for the first heating stage include: heating to 550℃-650℃ at a rate of 4.5℃ / min-5℃ / min and holding at that temperature for 25 min-35 min; and / or The conditions for the second heating stage include: heating to 1050℃-1150℃ at a rate of 2.5℃ / min-3.5℃ / min and holding at that temperature for 25 min-35 min; and / or The conditions for the third heating include: heating to 1200℃-1300℃ at a rate of 1.5℃ / min-2.5℃ / min and holding at that temperature for 2 h-3 h.

10. The application of the high-voltage insulator ceramic according to any one of claims 1 to 3 in the preparation of external insulation products for high-voltage transmission lines and power station equipment.